2012
DOI: 10.1152/ajpheart.00311.2011
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microvascular dysfunction in a porcine model of early atherosclerosis and diabetes

Abstract: van den Heuvel M, Sorop O, Koopmans SJ, Dekker R, de Vries R, van Beusekom HM, Eringa EC, Duncker DJ, Danser AH, van der Giessen WJ. Coronary microvascular dysfunction in a porcine model of early atherosclerosis and diabetes. Am J Physiol Heart Circ Physiol 302: H85-H94, 2012. First published October 7, 2011 doi:10.1152/ajpheart.00311.2011.-Detailed evaluation of coronary function early in diabetes mellitus (DM)-associated coronary artery disease (CAD) development is difficult in patients. Therefore, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 63 publications
9
46
2
1
Order By: Relevance
“…However, in two subsequent studies in Yorkshire × Landrace and Yorkshire pigs, respectively, diabetes was accompanied by augmented hypercholesterolaemia. In the first of these studies, van den Heuvel et al reported increased atherosclerosis in abdominal aortas [26], but in the other, Hamamdzic et al observed no effect on intimal area, intima/media ratio or the degree of stenosis of the coronary arteries, although the lesions were reported to be more complex in diabetic compared with control animals [25]. In the latter study, an approximately 50% reduction in body weight was also reported for the diabetic pigs compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in two subsequent studies in Yorkshire × Landrace and Yorkshire pigs, respectively, diabetes was accompanied by augmented hypercholesterolaemia. In the first of these studies, van den Heuvel et al reported increased atherosclerosis in abdominal aortas [26], but in the other, Hamamdzic et al observed no effect on intimal area, intima/media ratio or the degree of stenosis of the coronary arteries, although the lesions were reported to be more complex in diabetic compared with control animals [25]. In the latter study, an approximately 50% reduction in body weight was also reported for the diabetic pigs compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, diabetes has been reported to augment cholesterol levels in Yucatan and Sinclair minipigs [22,23]. In the widely used Yorkshire pig model of diabetes, inconsistent results have been obtained regarding the effect of diabetes on atherosclerosis and cholesterol level [24][25][26]. Impairment of kidney function and severe weight faltering in animal models of diabetes may further obscure the link between hyperglycaemia and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in light of increasing evidence that coronary microvascular dysfunction is present in a variety of coronary vascular disease states (19), with evidence of reduced NO/cGMP signaling (40) and increased ET signaling (36). Those observations have fueled the concept that microvascular dysfunction is an important component of, and contributor to, myocardial ischemia in patients with coronary artery disease (28).…”
Section: Integrated Control Of Coronary Resistance Vessel Tone In Swimentioning
confidence: 98%
“…Significance with Respect to Existing Methods Another method commonly used to assess changes in regulation of vascular tone is the use of isolated coronary and pulmonary small arteries or arterioles in a pressure or wire myograph 6,14,21 . The advantage of myograph studies is that vessels can be studied independent of surrounding tissue and without potentially confounding effect from circulating factors.…”
Section: Interpretation and Limitationsmentioning
confidence: 99%
“…Several swine models of cardiopulmonary disease, such as diabetes 6 , myocardial infarction 22 , pulmonary hypertension 8,9 and pacing induced heart failure 10 are available and could be combined with chronic instrumentation. A potential drawback is that, when commercially available swine breeds such as Yorkshire, Landrace, Large White etc, are used, adult swine are very large and may therefore be difficult to handle.…”
Section: Future Applicationsmentioning
confidence: 99%